Moss transcription factors regulating development and defense responses to stress. (15th February 2022) - Reboledo, Guillermo; Agorio, Astrid; Ponce De León, Inés
Abstract: Transcription factors control gene expression, leading to regulation of biological processes that determine plant development and adaptation to the environment. Land colonization by plants occurred 450–470 million years ago and was accompanied by an increase in the complexity of transcriptional regulation associated to transcription factor gene expansions. AP2/ERF, bHLH, MYB, NAC, GRAS, and WRKY transcription factor families increased in land plants compared with algae. In angiosperms, they play crucial roles in regulating plant growth and responses to environmental stressors. However, less information is available in bryophytes and only in a few cases is the functional role of moss transcription factors in stress mechanisms known. In this review, we discuss current knowledge of the transcription factor families involved in development and defense responses to stress in mosses and other bryophytes. By exploring and analysing the Physcomitrium patens public database and published transcriptional profiles, we show that a high number of AP2/ERF, bHLH, MYB, NAC, GRAS, and WRKY genes are differentially expressed in response to abiotic stresses and during biotic interactions. Expression profiles together with a comprehensive analysis provide insights into relevant transcription factors involved in moss defenses, and hint at distinct and conserved biological roles between bryophytes and angiosperms. Abstract : We review current knowledge on transcription factor families that regulate development and responses to biotic and abiotic stress in mosses and other bryophytes, highlighting their conserved and distinct biological functions compared with other plants.